Corruption and corruption control: democracy in the balance - Andersson, Staffan (Routledge Taylor & Francis Group, 2019)
Democratic governance, corruption and corruption control -- What corruption was, is, and is not -- Can we know how much corruption there is? : On the measurement of corruption -- Corruption control in public administration -- The connection between public integrity and democratic governance : four case studies -- Is corruption inevitable? : Can it be controlled? -- The future of public integrity.